Manajemen Pengembangan terhadap Program Pembelajaran Pendidikan Agama Islam di SMPN 25 Bulukumba - Nurul Hidayah Alimuddin; Abd. Aziz Muslimin; Muhlis Madani (CV. Ulil Albab Corp, 2022)
Management is a series of activities that must be completed following the given role through certain stages of implementation. Without understanding the function of good management, a manager will not be able to lead the organization into a successful organization because management is a determining factor for the success of an institution. This study aims to identify the management of the development of Islamic religious education learning programs at SMPN 25 Bulukumba. This study uses a qualitative descriptive method with data collection methods through observation, interviews, and literature study. In this study, the main informants were teachers of Islamic religious education subjects. The results showed that the development of Islamic religious education learning programs at SMPN 25 Bulukumba was supported by intracurricular and extracurricular activities. PAI learning program management is prepared and implemented based on the 2013 curriculum by considering 4 things: time allocation and the academic calendar, preparation of annual programs, semester programs, and learning implementation plans. In the development of PAI learning programs, found the inhibiting factors and also supporting factors in the development of the program were influenced by internal factors and external factors. Internal factors come from the student's condition while external factors are influenced by the family, environment, and inadequate time allocation. With the discovery of the inhibiting factors in the development of PAI learning programs at SMPN 25 Bulukumba, it is hoped that in the future they can be overcome so that the management of developing PAI learning programs at SMPN 25 is better.